The Impact of Monetary Policy on Labor Absorption in the Trade and Industry Sectors - Elia Nurul Mahmudah; Wildan Syafitri (Contemporary Studies in Economic, Finance and Banking, 2025)
The research explores the impact of monetary policy on employment in the trade and industry sectors in Indonesia from 1990 to 2023. The trade and industry sectors were chosen due to their significant roles in the national economy, however both are heavily impactd by macroeconomic policies, particularly monetary policy. This study utilizes the Mundell-Fleming model to explore the interactions between the goods market and the money market, as well as how monetary policy affects economic output and labor absorption. By employing the Vector Error Correction Model (VECM), it aims to address the long-term relationship between monetary policy and labor absorption while also accounting for short-term dynamics. Although there are numerous studies on the impact of monetary policy on macroeconomic variables such as inflation and economic growth, there remains a research gap in understanding the specific effects on employment in these sectors. This study aims to fill that gap by providing a more focused and comprehensive analysis, as well as presenting strategic implications for more effective policymaking in creating jobs and supporting sustainable economic growth.